Theory and Applications of Dynamic Games A Course on Noncooperative and Cooperative Games Played over Event Trees - Parilina, Elena; Reddy, Puduru Viswanadha; Zaccour, Georges (Theory and Decision Library C, Game Theory, Social Choice, Decision Theory, and Optimization, 2022)
XIII, 259 p. 39 illus., 9 illus. in color.